2019
DOI: 10.22452/jummec.vol22no1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vision Screening Training Module in Improving the Level of Knowledge on Vision Screening Among Pre-School Teachers in Klang Valley Malaysia

Abstract: Empowering lay screeners, such as preschool teachers, on vision screening is a cost-effective way to ensure larger populations of children can be screened. Although the validity of lay screeners in conducting vision screening were reported in several studies, none showed data concerning improvement of the level of knowledge among lay screeners after completing vision screening training, which could indicate the effectiveness of the training program. This study aimed to determine the level of knowledge of presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In collaboration with other stakeholders, the Health Ministry can implement an awareness program on uncorrected refractive error and amblyopia. Previous studies have shown the effectiveness of conducting vision screening at an early age [27][28][29][30]. Good vision will enable children to do better in school and can facilitate teaching and learning [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with other stakeholders, the Health Ministry can implement an awareness program on uncorrected refractive error and amblyopia. Previous studies have shown the effectiveness of conducting vision screening at an early age [27][28][29][30]. Good vision will enable children to do better in school and can facilitate teaching and learning [31,32].…”
Section: Discussionmentioning
confidence: 99%